Induction and Regulation of the Innate Immune Response in Helicobacter pylori InfectionSummary - Alain P. Gobert; Keith T. Wilson (Cellular and Molecular Gastroenterology and Hepatology, 2022)
Gastric cancer (GC) is the fifth most common cancer and the fourth most common cause of cancer-related death worldwide. The intestinal type of GC progresses from acute to chronic gastritis, multifocal atrophic gastritis, intestinal metaplasia, dysplasia, and carcinoma. Infection of the stomach by Helicobacter pylori, a Gram-negative bacterium that infects approximately 50% of the world’s population, is the causal determinant that initiates the gastric inflammation and then disease progression. In this context, the induction of the innate immune response of gastric epithelial cells and myeloid cells by H. pylori effectors plays a critical role in the outcome of the infection. However, only 1% to 3% of infected patients develop gastric adenocarcinoma, emphasizing that other mechanisms regulate the localized non-specific response, including the gastric microbiota and genetic factors. This review summarizes studies describing the factors that induce and regulate the mucosal innate immune response during H. pylori infection.